Pengaruh Penerapan Corporate Social Responsibilty (CSR) Terhadap Reaksi Investor Pada Perusahaan Go Publik Di Bursa Efek Indonesia - Juned, Sudarto (Ekonomika, 2010)
This study aim to see the effects of the application of CSR with investors reaction in Indonesia Stock Exchange (BEI). CSR benefits untils 1990s was a warm debate. The counter party states that CSR is seen as a cost and something that is not useful. This research uses dependent variables of individual daily stock returns (Rit) and the individual daily market return (RMT), abnormal return (AR), average abnormal return (AAR). The independent variables approachable with PROPER issued by the ministry of Environment (KLH). This study also used the intervening variables using Tobins Q. Implementation of CSR has a positive impact and significant market reaction(with Î²2 = 0,356 P= 0,004). Implementation of CSR has a positive influence on performance and significant (Î²1 = 0,871 with p=0.000). Mediating the companys performance positivelyÂ  and significantly influence the market reaction CSR (CSR indirect effect to the AR through the TQ for 0.465>0,08).Key Words: Corporate Social Responsibilty (CSR), the individual daily market return (RMT), abnormal return (AR), average abnormal return (AAR), Tobins Q, PROPER, Ministry of Environment (KLH).